Polyploid Giant Cancer Cells (PGCCs): The Evil Roots of Cancer - Chen, Junsong; Niu, Na; Zhang, Jing; Qi, Lisha; Shen, Weiwei; Donkena, Krishna V.; Feng, Zhenqing; Liu, Jinsong (Current Cancer Drug Targets, 2019)
Polyploidy is associated with increased cell size and is commonly found in a subset of adult organs and blastomere stage of the human embryo. The polyploidy is formed through endoreplication or cell fusion to support the specific need of development including earliest embryogenesis. Recent data demonstrated that Polyploid Giant Cancer Cells (PGCCs) may have acquired an activated early embryonic-like program in response to oncogenic and therapeutic stress to generate reprogrammed cancer cells for drug resistance and metastasis. Targeting PGCCs may open up new opportunities for cancer therapy.
Keywords: reprogramming